2014
DOI: 10.1584/jpestics.d13-073
|View full text |Cite
|
Sign up to set email alerts
|

A bioassay evaluation of pyroxasulfone behavior in prairie soils

Abstract: Pyroxasulfone behavior in prairie soils was evaluated using a 7-day sugar beet (Beta vulgaris L.) shoot length inhibition bioassay. Pyroxasulfone bioactivity in soil, assessed from 0 to 184 g a.i./kg, was primarily related to organic carbon content (p=0.001) with decreased bioactivity occurring in soils of high organic carbon. Pyroxasulfone bioactivity, measured after soil pH adjustments, was reduced as soil pH decreased demonstrating that at low soil pH pyroxasulfone becomes less available to plants. Pyroxasu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Pyroxasulfone is a residual, soil‐applied, pre‐emergent herbicide for the control of annual ryegrass ( Lolium rigidum Lam. ), barley grass ( Hordeum leporinum ), annual phalaris ( Phalaris minor ), silver grass ( Vulpia bromoides ) and toad rush ( Juncus bufonius ), and the suppression of certain grass weeds in wheat (not durum wheat) and triticale . Pyroxasulfone is an isoxazoline herbicide with a mode of action that inhibits cell division and very‐long‐chain fatty acids synthesis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyroxasulfone is a residual, soil‐applied, pre‐emergent herbicide for the control of annual ryegrass ( Lolium rigidum Lam. ), barley grass ( Hordeum leporinum ), annual phalaris ( Phalaris minor ), silver grass ( Vulpia bromoides ) and toad rush ( Juncus bufonius ), and the suppression of certain grass weeds in wheat (not durum wheat) and triticale . Pyroxasulfone is an isoxazoline herbicide with a mode of action that inhibits cell division and very‐long‐chain fatty acids synthesis …”
Section: Introductionmentioning
confidence: 99%
“…), barley grass (Hordeum leporinum), annual phalaris (Phalaris minor), silver grass (Vulpia bromoides) and toad rush (Juncus bufonius), and the suppression of certain grass weeds in wheat (not durum wheat) and triticale. [28][29][30] Pyroxasulfone is an isoxazoline herbicide with a mode of action that inhibits cell division and very-long-chain fatty acids synthesis. 31,32 Lafond et al 33 reported significant economic and crop management advantages, such as faster harvest and easier seeding, when crops were cut high at harvest, then seeded between the residue rows in the following season.…”
Section: Introductionmentioning
confidence: 99%
“…Higher rates of pyroxasulfone were required to achieve similar control of wild oats and false cleavers ( Galium spurium L.) at locations in Alberta and Saskatchewan as soil organic matter increased (Tidemann et al 2014). Szmigielski et al (2014) measured pyroxasulfone bioactivity across 25 different prairie soils and reported decreased activity in soils with low pH, although Westra et al (2014) observed no correlation between soil adsorption and soil acidity. Pyroxasulfone is nonionizable, and therefore soil pH does not affect dissociation.…”
mentioning
confidence: 99%
“…(1 (King and Garcia 2008) has been observed; however, both studies were conducted on high pH soils ( ]8) which may have affected weed control (Szmigielski et al 2014).…”
mentioning
confidence: 99%